Crop Substitution and Diversification Strategies : Empirical Evidence from Selected Brazilian Municipalities - Vargas, Marco Antonio; Ramos Campos, Renato (World Bank, Washington, DC, 2013)
This report looks at crop substitution and diversification strategies adopted in Brazil to foster the transition from tobacco to alternative crops. It analyzes the efforts undertaken in some Brazilian municipalities to support small-scale family farmers in their transition from tobacco to other sustainable livelihoods. This analysis comprises three case studies in selected municipalities in the South region of Brazil: Santa Cruz do Sul, Schroeder and Santa Rosa de Lima. Although all are located in the two main tobacco-producing states, Rio Grande do Sul and Santa Catarina, these municipalities show different degrees of economic dependence on tobacco and differences in their forms of insertion in the tobacco agro-industrial chain in Brazil.